OP0185 Immunohistologic study of synovitis from patients with undifferentiated arthritis who evolved to rheumatoid artrhitis or psoriatic arthritis after follow-up. (15th June 2017) - Aguilera, A Cuervo; Celis, R; Ramírez, J; Hernández, MV; Ruíz-Esquide, V; Inciarte-Mundo, J; Sanmartí, R; Cañete, JD
Abstract : Background: Undifferentiated Arthritis (UA) is defined as an inflammatory oligo/poly arthritis that does not fulfil criteria for a definitive diagnosis.Delay in diagnosis and treatment leads to poor prognosis. Previous studies have found differences in the cellular infiltrate between the synovitis of Rheumatoid Arthritis (RA) and Spondyloarthritis, including psoriatic arthritis (PsA) Objectives: To identify synovial biomarkers that may be useful to diagnose patients with early UA Methods: Retrospective longitudinal study.Patients with UA followed in our Arthritis Unit, who underwent arthroscopy between 2000 and 2014.Synovial biopsy were stained by immunohistochemistry with the following antibodies:CD3 for T cells, CD20 for B cells, CD79 for B cells, CD138 for plasma cells, CD31 for vessels, CD68 for macrophages, CD15 for neutrophils, CD117 for mast cells and hsp47 for fibroblasts, and quantified by Digital Image Analysis (Olympus).The same antibodies were evaluated in RA and PsA control groups Results: 55 UA and 78 controls were included.Table 1 shows the clinical, serological and demographic characteristics.Among patients with UA, 23 (42%) patients met criteria for RA and 32 (58%) for PsA during follow-up.Synovitis of patients with UA had higher macrophage (CD68+) density in total tissue (p=0.008) and sublining (SL) (p=0.012) than the control group.The UA that evolved to RA had a higher density of CD3 T lymphocytes than the control RA group (p=0.014). No differences were observed in cells of adaptive immunity (CD20 B lymphocytes, CD138 plasma cells), innate immunity (CD117 mast cells, CD15 neutrophils), vessels (CD31) between the 4 groups.The area (%) stained by anti-hsp47 (synovial fibroblasts) in SL was higher in the RA control group than in the PsA (p=0.003) Conclusions: This is the first immunohistological study of synovitis in a significant group of patients with UA who developed AR or PsA during follow-up. Although there are some differences between the UA and control groups in the density of CD68+ macrophages and lymphocytes T CD3+, these do not appear to be useful for an early diagnosis of UA. On the other hand, unlike the results of some previous studies, we not found differences between the cellular infiltrate (adaptive immunity, innate immunity or vessels) in patients with RA and PsA. The fact that some patients with UA were undergoing treatment prior to synovial biopsy and its retrospective character limit the results of this study Acknowledgements: Financed: "Fondo de Investigaciόn Sanitaria" (PI14/00785. JD Cañete) del Instituto de Salud Carlos III (ISCIII). Co-financed by BECA FER-2015. Premis "Emili Letang", Hospital Clínic. BECA MSD-Sociedad Catalana de Reumatología Disclosure of Interest: None declared